Continuous detection of Chikungunya Virus in a passive surveillance system in southern Thailand, 2012-2019. - Aaron Farmer; Kathryn B Anderson; Darunee Buddhari; Thanaporn Hortiwakul; Boonsri Charernmak; Butsaya Thaisomboonsuk; Tippa Wongstitwilairoong; Taweewun Hunsawong; Chonticha Klungthong; Piyawan Chinnawirotpisan; Sarunyou Chusri; Stefan Fernandez (PLoS Neglected Tropical Diseases)
Chikungunya virus (CHIKV) infections are distributed across the globe, causing significant and, often, lasting morbidity. CHIKV vaccines are in development, but their evaluation is limited by the unpredictability of CHIKV transmission, which classically manifests as explosive epidemics separated by variable interepidemic periods. A passive surveillance study for undifferentiated febrile illness was established in southern Thailand in 2012 and is ongoing. Among 1466 febrile individuals with acute and convalescent specimens, 398 (27.1%) had molecular or serological evidence of acute CHIKV infection. The proportions of participants confirmed to have CHIKV infection differed by year, being highest during epidemic periods (41.1% in 2018-2019, corresponding to a large regional CHIKV outbreak, compared to 19.3% in 2012-2017). These data suggest persistent circulation of CHIKV in the study area, though additional studies are needed to confirm these findings and to discern whether this persistence reflects widespread, low-level transmission or migrating bursts of focal epidemic activity.